Metode SAW (Simple Additive Weighting) Untuk Pemilihan Karyawan Terbaik - Kusdarnowo Hantoro; Andy Achmad Hendharsetiawan; Ajif Yunizar Pratama Yusuf (Journal of Informatic and Information Security, 2021)
The purpose of determining the best employees is as an appreciation for employee performance so as to motivate employees to be able to work optimally and be able to survive in the organization for a long time. Although the goal is very simple, however, the process turns out to be very complex, takes quite a long time and costs quite a bit so that this creates the opportunity for errors to occur in determining who is the right person. Especially if the company has employees with abilities that are not much different from other employees, the determination is sometimes very subjective. Actually there are several assessment criteria in the decision-making process for selecting the best employees, namely: an assessment based on the criteria for attendance, loyalty, and tardiness and employee performance. Because it is necessary to build a system that can assist decision making to determine the selection process objectively by using the SAW (Simple Additive Weighting) method.